Reimagining the High-Density, Vertical 15-Minute City - Chenyu Zan; Ruchi Bhatia; Swinal Samant (Buildings)
In recent years, the 15-minute city (15MC) model has gained significant attention among scholars and practitioners, particularly in the wake of COVID-19. However, limited research has explored how this model can be adapted to high-density, high-rise urban environments characterized by compact land use and mobility challenges. This study addresses this gap by extending the core principles of the 15MC—density, proximity, diversity, and digitalization—with additional context-specific dimensions: mobility choice, walkability and cyclability, public transport proximity, inclusivity, placemaking, and policy integration. Using qualitative research and site observations, we analyze three diverse neighborhoods in Singapore: Clementi, Toa Payoh, and Holland Village. The comparative evaluation reveals the strengths and limitations of applying a vertical, hierarchical, and multilayered planning model in dense urban contexts. The study also highlights the potential of a three-dimensional planning framework that integrates vertical and horizontal spatial structures to optimize accessibility and functionality. The findings contribute to the broader discourse on sustainable urbanism by offering actionable strategies to support the transition toward more accessible, low-carbon, and livable high-density cities.